Ten years of struggle,victories and dreams = Diez años de luchas, conquistas y sueños. - National Confederation of Bank Workers (CNB) (São Paulo : CNB, 2002)
Bibliotheek François Vercammen
Meertalig
Monografie
Keywords: sociale strijd; banksector; Brazilië